THE EFFECTIVENESS OF EXTENSION USING AUDIO-VISUAL MEDIA ON INCREASING CADRE KNOWLEDGE ABOUT PHBS (CLEAN AND HEALTHY LIVING BEHAVIOR) - Habibullah Mustofa; Ni Luh Diah (Indonesian Journal of Health Care Management, 2021)
Clean and Healthy Life Behavior (PHBS) is all health behavior carried out on awareness so that family members or families can help themselves in the health sector. The effectiveness of this program can be achieved if supported by all elements of society, especially health cadres in each village. Efforts can be made to increase cadre knowledge by providing counseling using audio-visual media. The purpose of this study was to analyze the increase in knowledge of  cadres about PHBS before and after counseling with audio-visual media. This study uses a correlative research design while the sampling technique used in this study is total sampling. The sample in this study amounted to 28 peoples. Based on the analysis test with the Paired Samples T-Test with α 0.05 the results of Sig. (2-tailed) of 0.022. From the results of the test, it was found that the value of Sig. (2-tailed) <α (0.05). Because of the value of Sig. (2-tailed) <α, then Ho is rejected, which means there is a difference in the level of understanding/knowledge of respondents to PHBS before and after counseling with audio-visual media. There was an increase in respondents' understanding of PHBS after being given counseling with audio-visual media, where the level of understanding/positive knowledge of respondents towards PHBS increased from 21% to 36%. Based on the results of this study, it is recommended that there be a comprehensive provider of information to each cadre to increase knowledge.